(3JbQjH GdebQHs - (3CHhMjGf CKjQGdOjf eMeO Hf jhSa Hf Ydj Hf MjGf GdfaRj GdZQfGWj GdfMhjs; (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s
(3ChdgG (B:s
(3hHYO, aNjQ GdcdGe eG JQJHJ CUhdg hJgPHJ aUhdg hbO LeYJ aj gPg GdChQGb ef cJGH GdebQH faGFSg s
(3BNQgG (B:s
(3hHJCNjQ MQa Yf MQa, Ch HYV cdGe Yf cdGe hdG jfbGS EdG eG cKQ fLR GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3aj GdeYgO fSNI CNQi GfXQgG aj GdLRA GdChd HQbe (B38 (3fMhs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs